Computational Design and Study of Artificial Selenoenzyme with Controllable Activity Based on an Allosteric Protein Scaffold. Issue 44 (11th June 2019) - Li, Siyuan; Xu, Wanjia; Chu, Shengnan; Ma, Ningning; Liu, Shengda; Li, Xiumei; Wang, Tingting; Jiang, Xiaojia; Li, Fei; Li, Yijia; Zhang, Dongmei; Luo, Quan; et al.
Abstract: The establishment of new enzymatic function in an existing scaffold is a great challenge for protein engineers. In previous work, a highly efficient artificial selenoenzyme with controllable activity was constructed, based on a Ca 2+ ‐responsive recoverin (Rn) protein. In this study, a design strategy combining docking, molecular dynamics, and MM‐PBSA is presented, to predict the catalytically active site of glutathione peroxidase (GPx) on the allosteric domain of Rn. The energy contributions of the binding hot spot residues are evaluated further by energy decomposition analysis to determine the detailed substrate recognition mechanism of Rn, which provides clear guidance for artificial enzyme design for improved substrate binding (Michaelis–Menten constant, K m ). Abstract : Artificial enzymes : A computational protocol that combines docking, MD simulation, and MM‐PBSA analysis is proposed to design a GPx‐like active site in Ca 2+ ‐responsive recoverin for the construction of a highly efficient artificial selenoenzyme with controllable activity (see figure). This method gives clear guidance for de novo enzyme design based on a non‐homologous protein scaffold.